Utilization of Antithrombotic Medicines in Primary Prevention and Risk Assessment of Deep Vein Thrombosis at a Tertiary Care Teaching Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Deep vein thrombosis (DVT) and pulmonary embolism (PE) are common preventable conditions often associated with high morbidity if not treated promptly. Evaluation of antithrombotic drugs is essential in considering the spectrum of use and the risks associated with their therapy in patients with DVT. Therefore, this study was undertaken to evaluate the usage pattern of antithrombotics and assessment of DVT risk in primary prevention of DVT at a tertiary care teaching hospital.Materials and Methods:It was an observational, prospective and single-center study carried out over a period of 18 months. Out of 26,687 hospitalized patients assessed for eligibility as per Wells' score. Only 186 patients met inclusion criteria, but 164 patients were analyzed for primary prevention and risk assessment of DVT.Results:Out of 164 patients of primary prevention of DVT, 54 (32.92%) patients were given thromboprophylaxis for DVT. Out of 54 patients, 23 patients were given warfarin either alone or in combination with other drugs, whereas aspirin was given as a single drug in two patients only. No modification in the treatment of either anticoagulant or antiplatelet drugs was observed in patients for primary prevention of DVT (n= 54). As per Wells' score, 87 patients were considered to be “high” risk of DVT, but only six patients developed DVT versus, whereas 31 patients were considered to be of “moderate” risk, only two patients developed DVT.Conclusion:Few patients of primary prevention of DVT received adequate antithrombotic thromboprophylaxis. Heparin and warfarin were mainly used for thromboprophylaxis of DVT. DVT prophylaxis is very important and thromboprophylaxis is the mainstay of treatment among patients of primary prevention of DVT.